Scaling Down Effect on Low Frequency Noise in Polycrystalline Silicon Thin-Film Transistors - Yuan Liu (IEEE, 2019)
Scaling down effects on conduction and low frequency noise characteristics are investigated in a set of p-type polycrystalline silicon thin-film transistors (poly-Si TFTs) with fixed channel width ( $W=8 μ$ m) and different channel lengths ( $L=2, 4, 8, 12, ~\text{and}~ 20 μ$ m). First, short channel effects on threshold voltage, field effect mobility, and sub-threshold swing are examined, while the presence of contact may induce to the degradation of field effect mobility in the short channel devices. Subsequently, the drain current noise power spectral densities are measured at varied effective gate voltages and drain currents. The slopes of normalized noise against effective gate voltage are varied from −1.1 to −2 with decreasing channel length, which indicates that poly-Si TFTs varied from bulk dominated devices to interface dominated devices. Based on $Δ N-Δ μ$ model, the flat-band voltage noise spectral density and coulomb scattering coefficient are extracted. Therefore, measured normalized noises are simulated by considering of contact resistance. Finally, short channel effects on some noise parameters (such as Hooge’s parameter, etc.) are studied and discussed.